Global Warming: Facing Confirmation Bias and Cognitive Dissonance with Hands-on Activities - Ã…Â lÃƒÂ©grovÃƒÂ¡, LeontÃƒÂ½na; Ã…Â lÃƒÂ©gr, Jan; StudniÃ„Âka, Filip (International Journal of Research in STEM Education, 2020)
Although global warming is an irrefutable scientific fact, many people, including those who often call themselves skeptics and critical thinkers, are doubtful about this unambiguous fact. An extensive longitudinal survey amongst the students showed that even future teachers are not resistant to these misconceptions, even if they are presented with the conclusions of the scientific studies. In this paper, we show simple hands-on classroom activities in which publicly available climate data are studied with methods previously known to students, and simple atmospheric models are presented. These simple exercises can help future teachers to establish their own opinion on global warming based on the analysis of data and physical models and not on information from obscure websites and social networks.